The right to property (1917-1957). Constitutional and jurisprudential análisis - Brito Melgarejo, Rodrigo (2023)
Within a constitutional state, the right to property is a central element. With the 1917 Constitution, issued after the Mexican Revolution, its regulation was made through articles 14 and 27 of the Constitution, primarily focused on dismantling the Porfirian latifundia, achieving agrarian distribution in order to eliminate the concentration of land in few hands, and privileging the collective interest over the private interest, as well as the participation of the State. It was in this sense that the wording of the fundamental text was established. With regard to the Court and the criteria issued during the fifth period (1917-1957) on the aforementioned articles, it is observed that they maintain the postulates tending to satisfy the social demands made since the revolutionary period together with the permanence of individual property.